(untitled) (Journal of the College of Basic Education, 2023)
The great scientific and technological progress witnessed by the world at the present time has led to several changes in the lives of individuals and societies and in different aspects of life. Scientific knowledge in specialized work in general is one of the most important pillars that researchers seek to deepen in order to reach new scientific contexts that deepen vision in the specialized field.